PENGEMBANGAN DAN VALIDASI KUESIONER UNTUK MENGIDENTIFIKASI FAKTOR PENYEBAB PERILAKU PENGGUNAAN ANTIBIOTIK TANPA RESEP DOKTER - Eko Setiawan; Dewi Paskalia Andi Djawaria; Adji Prayitno (Fakultas Farmasi Universitas Pancasila, 2018)
Factors attributing to the behavior of non-prescription used of antibiotics in Indonesia setting have not been identified yet. The availability of effective and efficient instrument or method to identify the attributing factors might be the cause of non-optimal identifying process. The objective of present study was to develop instrument, i.e questionnaire, to identify factors contributing to the behavior of non-prescription used of antibiotics. The questionnaire was developed based on factors identified on published scientific literatures. Face and content validity were conducted by having the experts’ judgement, while the construct validity was conducted by using the Spearman Correlation Test. Reliability was tested by using Cronbach’s alpha test. There were 14 rating and 8 multiple answer questions in the questionnaire that could be classified unto 5 domains. After conducting the validity and reliability test, the final questionnaire had a R value 0.276-0.628 and Cronbach’s alpha 0.833. This valid and reliable questionnaire could be used to portray the attributing factors of non-prescription used of antibiotics in larger area, therefore, the most appropriate intervention could be planeed based on the identified factors.